Late Miocene tortoises from Samos, Greece: implications for European Neogene testudinid systematics and distributions. Issue 6 (2nd November 2019) - Vlachos, Evangelos; Pérez-García, Adán; Roussiakis, Socrates; Georgalis, Georgios L.; Kear, Benjamin P.
ABSTRACT: The world-famous upper Miocene fossil localities on the Aegean island of Samos in Greece have produced a rich fossil record that sheds light on the evolution of eastern Mediterranean terrestrial faunas over a one-million-year interval of the late Neogene. Fossils have been discovered on Samos since antiquity, although a succession of paleontological and commercial collecting expeditions over the last 130 years has resulted in specimens now being distributed throughout museums all over the world. Here, we survey the fossil tortoise remains from Samos, which are significant because they include early antecedents of the modern Testudo lineage, together with spectacular examples of the European Neogene gigantic testudinid † Titanochelon, which represents one of the largest-bodied terrestrial turtle taxa documented to date. All of the Samos fossils derive from the Mytilinii Formation, which spans the late MN11–early MN13 Neogene land mammal zones. The small-bodied tortoise remains include two incomplete shells that are morphologically consistent with basal testudonans and phylogenetically distinct from the coeval species Testudo marmorum found on mainland Greece. The Samos gigantic tortoise †' Testudo ' schafferi was based on a spectacularly large skull and femur. However, we describe new plastron fragments, limb elements, and osteoderms that are compatible with † Titanochelon specimens from southern Greece and Anatolia. This could imply faunal links with the distinctive 'Pikermian' local assemblages from Asia Minor and concurs with the proposed late Miocene–Pliocene biogeographic segregation of large mammals from the eastern Aegean margin and Turkey relative to those occurring in northwestern Greece and the Balkan Peninsula.